2014
DOI: 10.3390/ijms15069718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Tumor-Infiltrating Inflammatory Cells in Primary Small Cell Esophageal Carcinoma

Abstract: Primary small cell esophageal carcinoma is a rare and aggressive type of gastrointestinal cancer with poor prognosis. In the present study, the impact of tumour infiltrating inflammatory cells on clinico-pathological characteristics and the patients’ prognosis were analysed. A total of 36 small cell esophageal carcinomas, 19 adjacent normal tissues and 16 esophageal squamous cell carcinoma samples were collected. Qualified pathologists examined eosinophils, neutrophils, lymphocytes and macrophages on histochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…However, in addition to their important role in fighting infections and inflammation, they play a critical role in the development of effective antitumor immunity (31). The infiltration of neutrophils and/or eosinophils in colorectal and primary small cell esophageal carcinoma was found to be associated with a good prognosis and enhanced survival of patients (32)(33)(34). Studies using in vivo models reported that tumor-homing neutrophils and/or eosinophils were essential for tumor rejection by initiation of changes in the tumor microenvironment (35)(36)(37).…”
Section: Antitumor Effect Of the Combination Of Manumycin A Andmentioning
confidence: 99%
“…However, in addition to their important role in fighting infections and inflammation, they play a critical role in the development of effective antitumor immunity (31). The infiltration of neutrophils and/or eosinophils in colorectal and primary small cell esophageal carcinoma was found to be associated with a good prognosis and enhanced survival of patients (32)(33)(34). Studies using in vivo models reported that tumor-homing neutrophils and/or eosinophils were essential for tumor rejection by initiation of changes in the tumor microenvironment (35)(36)(37).…”
Section: Antitumor Effect Of the Combination Of Manumycin A Andmentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC) is the third most common malignancy of the digestive tract and the fifth leading cause of cancer‐related death worldwide . The prognosis of ESCC remains to be poor with 5‐year survival rate <20% .…”
Section: Introductionmentioning
confidence: 99%
“…2 Esophageal squamous cell carcinoma (ESCC) is the third most common malignancy of the digestive tract and the fifth leading cause of cancer-related death worldwide. [29][30][31][32][33][34][35][36] The prognosis of ESCC remains to be poor with 5-year survival rate <20%. [37][38][39][40][41] In this study, we found that NCOA1 is highly enriched in human ESCC, and the levels of NCOA1 are clinically important in ESCC progression and patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…SCCE is a highly aggressive disease characterized by rapid progression, extensive metastasis and poor prognosis, with a higher incidence of males than females (7)(8)(9)(10). At present, some studies have found a number of clinicopathological indicators that can assess the prognosis of SCCE, including lesions, TNM stage, VALSG stage, tumor inflammatory cell infiltration and treatment, but the results from some of these literatures are controversial (11)(12)(13)(14)(15). Therefore, it is necessary to explore new indicators that can evaluate the prognosis in order to improve the existing prognostic model and achieve a more accurate and comprehensive assessment of SCCE.…”
Section: Introductionmentioning
confidence: 99%